Direct Analysis of Plasma Fibrinogen-Derived Fibrinopeptides by High Performance Liquid Chromatography: Investigation of Aα-Chain N-Terminal Heterogeneity - Southan, Christopher; Thompson, Elizabeth; Lane, David A (Thrombosis and Haemostasis, 1986)
Fibrinopeptide A (FPA), released from the fibrinogen Aa-chain by thrombin, can be resolved by high-performance liquid chromatography (HPLC) into three forms, the intact peptide (A), a modified peptide phosphorylated at the serine in position 3 (AP), and an N-terminally degraded form (AY). A new method has been developed, using HPLC, that allows direct measurement of the proportions of AP, A, and AY released by thrombin from fibrinogen in plasma samples of 200 ul or less. The method was used to examine variations in the proportions of AP and AY expressed as a % of total FPA in a number of patient and control groups. The mean percentages of AP and AY of plasma fibrinogen were found to be 21.7 and 14.2%, respectively, in normal laboratory controls. In older, apparently normal, individuals these figures were 27.0 and 15.5%, respectively. Cord plasma exhibited very high AP and slightly reduced AY levels (41.6 and 12.4%, respectively) compared with normal adults. Patients with liver failure had low AP levels and high AY levels (11.6 and 21.1%, respectively). Patients, recovering from major surgery or acute thrombotic stroke showed an acute-phase rise in fibrinogen level that was accompanied by an increase in AP and variable reduction in AY. Incubation of heparinized whole blood for 8 days in vitro demonstrated a gradual decrease in the proportion of AP and increase in AY of plasma fibrinogen. These results provide some support for the idea that an increased “aging” of fibrinogen in the circulation may result in a decrease in the AP content of fibrinogen accompanied by a more variable increase in AY.
Keywords: Fibrinogen; Fibrinopeptides; HPLC